2020
DOI: 10.3389/fmicb.2020.510638
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Analysis of O-Antigen-Specific Bacteriophage P22 Inactivation by Salmonella Outer Membrane Vesicles

Abstract: Bacteriophages use a large number of different bacterial cell envelope structures as receptors for surface attachment. As a consequence, bacterial surfaces represent a major control point for the defense against phage attack. One strategy for phage population control is the production of outer membrane vesicles (OMVs). In Gram-negative host bacteria, O-antigen-specific bacteriophages address lipopolysaccharide (LPS) to initiate infection, thus relying on an essential outer membrane glycan building block as rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 70 publications
3
14
0
Order By: Relevance
“…In agreement with the proposed role for OMV tRFs in combatting phage infection, the ability of OMVs to inhibit phage infection of several bacterial species (e.g. E. coli 21 , P. marinus 22 , S. exneri 23 , S. enterica 24 , and V. cholerae 25 ) has now been reported. What's more, in addition to the con rmation that S. Typhimurium OMVs contain signi cant levels of tRFs reported here, tRFs have been reported to be signi cantly enriched in E. coli and P. aeruginosa OMVs.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In agreement with the proposed role for OMV tRFs in combatting phage infection, the ability of OMVs to inhibit phage infection of several bacterial species (e.g. E. coli 21 , P. marinus 22 , S. exneri 23 , S. enterica 24 , and V. cholerae 25 ) has now been reported. What's more, in addition to the con rmation that S. Typhimurium OMVs contain signi cant levels of tRFs reported here, tRFs have been reported to be signi cantly enriched in E. coli and P. aeruginosa OMVs.…”
Section: Discussionsupporting
confidence: 68%
“…In summary, despite there being several published reports now independently describing (1) roles for speci c tRFs in facilitating/inhibiting viral replication 3,[8][9][10]20 , (2) the marked prevalence of tRFs within secreted vesicles (both exosomes and OMVs) 11,14−18 , and (3) the ability of OMVs to inhibit phage infection of several bacterial species (e.g., E. coli 21 , Prochlorococcus marinus 22 , Shigella exneri 23 , Salmonella enterica 24 , and Vibrio cholerae 25 ) there have been no examinations of the effects of vesiclesecreted tRFs on viral infection reported to date. Therefore, in light of a study in 2020 that conclusively demonstrated the ability of Salmonella enterica serovar Typhimurium OMVs to defend against bacteriophage P22 24 , we recently elected to de ne the full repertoire of Salmonella enterica serovar Typhimurium tRFs and explore their potential involvement in combating bacteriophage predation.…”
Section: Introductionmentioning
confidence: 99%
“…As such, we recently screened small RNA-seq datasets for the presence of recurrent, specifically excised tRFs and identified 31 recurrent, relatively abundant tRFs expressed by S. Typhimurium. What's more, S. Typhimurium OMVs can inhibit P22 bacteriophage infection 24 , and we find S. Typhimurium OMVs contain significant levels of tRFs highly complementary to known Salmonella entericainfecting bacteriophage. Most notably, tRNA-Thr-CGT-1-1, 44-73, is 100% complementary to 29 distinct, annotated Salmonella enterica-infecting bacteriophage including P22, and this tRF is 100% conserved in E. coli (Supplemental Table 1).…”
Section: Discussionmentioning
confidence: 71%
“…Typhimurium OMV inhibition of P22 requires tRNA-Thr-CGT-1-1, 44-73 tRF S. Typhimurium OMVs were recently reported to inhibit bacteriophage P22 infection 24 . Therefore, in light of having found that tRNA-Thr-CGT-1-1, 44-73 tRF intracellular sequestration improves P22 infectivity, we next explored the potential role of tRNA-Thr-CGT-1-1, 44-73 tRF in OMV-mediated P22 restriction.…”
Section: Smentioning
confidence: 99%
See 1 more Smart Citation